1994
DOI: 10.1007/bf00019057
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of cytochrome c oxidase genes from the cyanobacterium Synechocystis sp. PCC6803: Evidence for alternative respiratory pathways

Abstract: An oligonucleotide directed against a highly conserved region of aa3-type cytochrome c oxidases was used to clone the cox genes from the cyanobacterium Synechocystis sp. PCC6803. Several overlapping clones were obtained that contained the coxB, coxA, and coxC genes, transcribed in the same direction in that order, coding for subunits II, I, and III, respectively. The deduced protein sequences of the three subunits showed high sequence similarity with the corresponding subunits of all known aa3-type cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…In addition, experiments with wild-type cells incubated with the photosynthetic inhibitor, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), did not affect Fe uptake rates but caused an increase in iron reduction rates (Supplementary Figure S2). As both photosynthetic and respiratory chains in cyanobacteria share a quinone/quinol pool (Schmetterer et al, 1994), the inhibition of photosynthesis may increase respiratory electron flow through Cytb 6 f. Does respiratory electron flow have a role in reductive iron uptake?…”
Section: Coordinated Transporter Activity C Kranzler Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, experiments with wild-type cells incubated with the photosynthetic inhibitor, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), did not affect Fe uptake rates but caused an increase in iron reduction rates (Supplementary Figure S2). As both photosynthetic and respiratory chains in cyanobacteria share a quinone/quinol pool (Schmetterer et al, 1994), the inhibition of photosynthesis may increase respiratory electron flow through Cytb 6 f. Does respiratory electron flow have a role in reductive iron uptake?…”
Section: Coordinated Transporter Activity C Kranzler Et Almentioning
confidence: 99%
“…Two of these-a cytochrome c oxidase (Cox) and a quinol oxidase (Cyd)-are important in cellular respiration (Alge and Peschek, 1993;Schmetterer et al, 1994;Howitt and Vermaas, 1998). The function of the third, the Alternate Respiratory Terminal Oxidase (ARTO), or CtaII, remained unclear.…”
Section: Coordinated Transporter Activity C Kranzler Et Almentioning
confidence: 99%
“…The existence ofa cytochrome c oxidase in cyanobacteria has been shown,5 7) and therefore the respiratory electron transport has been considered to pass through a cytochrome hlf complex and cytochrome ('553 (or plastocyanin). However, Schmetterer et al 8 ) have demonstrated that mutant strains of Synechocystis pec 6803. in which aa3-type oxidase was genetically destroyed, had significant respiratory oxygen uptake.…”
Section: Syn(!c/zocystis Pec 6803mentioning
confidence: 99%
“…Factors influencing the redox state of the PQ pool may therefore influence intracellular processes. To aid in studying these processes, a series of mutants with lesions in photosynthetic and respiratory proteins have been developed (7,11,17,28,29,32,33).…”
mentioning
confidence: 99%
“…One of these mutants lacks CtaI (32). This mutant is unable to grow at low light intensity, even in the presence of glucose, presumably because of overreduction of the PQ pool in thylakoids.…”
mentioning
confidence: 99%